High-Performance Zwitterionic Organohydrogel Fiber in Bioelectronics for Monitoring Bioinformation - Jun Xia; Jiabei Luo; Boya Chang; Chuanyue Sun; Kerui Li; Qinghong Zhang; Yaogang Li; Hongzhi Wang; Chengyi Hou (Biosensors, 2023)
Bioinformation plays an imperative role in day-to-day life. Wearable bioelectronics are important for sensing bioinformation in real-time and conductive hydrogel fibers are a key component in next generation wearable bioelectronics. However, current conductive hydrogel fibers have remarkable disadvantages such as insufficient conductivity, stability, and bioinformation sensing ability. Here, we report the synthesis of a zwitterionic organohydrogel (ZOH) fiber by the combination of the mold method and solvent replacement strategy. The ZOH fiber shows transparency (92.1%), stretchability (905.8%), long-term stability, anti-freezing ability (−35–60 °C), and low light transmission loss (0.17 dB/cm). Then, we integrate the ZOH fiber into fabric for use as a bioinformation sensor, the results prove its capability as a bioinformation monitor, monitoring information such as motion and bioelectric signals. In addition, the potential of the ZOH fiber in optogenetic applications is also confirmed.